Faktor-faktor yang Mempengaruhi Perilaku Membolos Siswa SMP - Yani, Desis Saputri; Sano, Afrizal (Lembaga Yasin AlSys, 2024)
This research is motivated by the existence of a number of factors that influence students' truant behavior at school. This research aims to describe the factors that influence the truancy behavior of students at SMPN 1 Lembah Gumanti in terms of: (1) the aspect of not going to school for days, (2) the aspect of not going to school without permission, (3) the aspect of frequently leaving during class hours. . certain things, (4) aspects of going to school on different days, (5) aspects of being invited by friends to go out for subjects you don't like, (6) aspects of not going to class after break time, (7) aspects of sending permission letters with made-up reasons. For. This type of research uses a quantitative approach with descriptive methods. The research sample used a total sampling technique of 90 people. The instrument used was a questionnaire. Data is processed using a percentage formula. The research results show the factors that influence students to skip class: (1) because they are not in a good mood, (2) because they are not enthusiastic about going to school, (3) because they don't get more pocket money, (4) because they are bored with the material presented. and the way the teacher teaches, (5) because he feels that the teacher who teaches is favoritism, (6) because his friend invited him to sit in the canteen during class time, (7) he left class time because he was invited by his friend, (8) because the class atmosphere was not pleasant, (9) stay in the canteen to eat, (10) because they are not interested in the next subject (11) because they don't do their school work, (12) because they are afraid of being punished if they don't come in without explanation.